METODA DRAMY W SZKOLNEJ EDUKACJI HISTORYCZNEJ - Kujawska, Maria (Wydawnictwo Naukowe UAM w Poznaniu, 1997)
The article deals with drama, one of the new in Poland, unconventional methods used in the teaching of history in Polish schools. Due to a variety of issues which lie within the theoretical scope of the method, the first part of the article presents the background, theoretical assumptions and functions of drama. The forthcoming article will cover a detailed discussion of drama techniques, together with some inspirations for their creative application during history lessons.
Keywords: metoda dramy; edukacja historyczna; aktywizacja ucznia; drama methods; education of history; activation of student; Neodidagmata